Introduction - Cass, Devon (2025)
Lars Moen, in The Republican Dilemma, argues that freedom as non-domination is either 1) undistinctive, involving the same directives for promoting freedom as the supposedly rival pure negative conception of freedom; or it is 2) unsuitable for modern society, being at odds with contemporary conditions of pluralism. Here I give a short precis of the book along with brief summaries of the other discussions in this symposium. Finally, I suggest a way in which I think the first horn of the dilemma can be resisted.